(untitled) (Microbes and Health, 2013)
A descriptive type of cross sectional study was conducted on 132 students of class IX and X of Mymensingh sadar upazilla during early April to late June, 2007. This study was performed to assess and compare the level of knowledge and practicing behavior of urban and rural students in regards to hand washing, bathing, tooth brushing and taking care of nail and hair. All the students were interviewed with a semi-structured questionnaire and observed with an observational check list. The mean age of the students was 14.5±0.94 years. The knowledge of the students regarding tube well water for drinking was significantly higher in rural area (98.3%) compared to urban area. In addition, tube well water was stated as safe for bathing by 77.3% and safe for washing by 80.3% students. Hand washing before meal with soap and water was found almost similar among urban and rural students but hand washing with soap and water after defecation was found significantly better practiced in urban (97.2%) students. Practice regarding tooth paste use was higher in urban (80.6%) area and charcoal use (10.0%) was still found in rural areas. The mean frequency of tooth brushing was significantly higher in girls (1.8±0.5) compared to boys (1.6±0.5) and was significantly higher among urban (1.9±0.4) students. Most of the students were found trimming their nail once a week (74.2%) and cut their hair once a month (85.6%). Overall trend of knowledge and practice about personal hygiene is in positive direction but urban students and girls were more aware about personal hygiene than rural students. DOI: http://dx.doi.org/10.3329/mh.v1i1.13712 Microbes and Health Vol.1(1) June 2012 pp.34-37